Social stigma and the quality of life among patients with schizophrenia - Anipah Anipah; Dewi Eka Putri; Basmanelly Basmanelly (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Schizophrenia is a mental illness or disorder experienced by most people in the world. The stigma that exists in society with mental disorders is very high, where family acceptance and family support are shown through attitudes, actions that will greatly affect the quality of life of schizophrenics.Purpose: To find out the relationship between community stigma, family acceptance and support with the quality of life of schizophrenics.Method: Using a descriptive cross-sectional correlation approach. The sample in this research is as many as 329 families at the Jambi Regional Mental Hospital polyclinic using purposive sampling technique. The questionnaire used was the Schizophrenia Quality Of Life Scale (SQOLS), The Devaluation Families Scale (DCFS), family acceptance and support. The analysis used is multiple linear regression.Results: The average age of the respondents was 35.99, ranging from 17 to 70 years. recurrence of schizophrenics 1 time per year and less than 5 years of care.Conclusion: There is a relationship between community stigma, family acceptance and support with the quality of life of schizophrenics with a p-value of 0.000 (<0.05). The dominant factor related to quality of life is family acceptance (OR = 0.534).Suggestion: It is hoped that in caring for schizophrenics the family can be involved as a caregiver as a support system.